PTU-202 Flexible sigmoidoscopy as a screening tool for bowel cancer- time for standardisation!. (28th May 2012) - Ahmed, I; Rutter, C; Hazeldine, S; Marden, P
Abstract : Introduction: Flexible sigmoidoscopy (FS) has been shown to offer substantial reduction in the incidences of and mortality from distal colorectal cancer and is soon to become the new screening method. Although quality markers for colonoscopy have been widely adopted in the UK, similar practice for FS is variable. In order for this procedure to be used as an effective screening tool it will need standardisation in term of quality assurance. Methods: It was a retrospective study which was carried out using an endoscopy database to identify patients who had FS performed during 2009–2011 in three district general hospitals serving a population of 600 000. The patient's age, sex, extent of examination, grade of endoscopist, use of medications, procedure tolerance, bowel visualisation and missed left sided lesions were investigated. A complete examination was defined as a procedure when the scope was passed to the splenic flexure or beyond. Mucosal visualisation and patient tolerance were graded as good, fair and poor. Results: A total of 2823 procedures were recorded, of which 87.5% were carried out as an out-patient. In 56.7% of cases the scope was passed to the splenic flexure or beyond, while examination was limited to descending colon in 20.2%, sigmoid colon in 18.7% and rectum in 4.6%. Poor bowel preparation accounted for procedure failure in 3.7%, pain for 1.5% and anatomical complexities and pathology encounter in 1%, while in 94.1%, there were no limitations. 94.8% of procedures were performed without sedation. Good mucosal visualisation was achieved in 76.1% and the procedure was well tolerated in 80.7%. 2% of the patients used entonox and 3.3% received midazolam (range 1–5 mg median dose 3 mg). Pathologies were detected in 58.8% of the cases while procedure was reported normal in the remaining 41.2 %. No patient had a subsequent diagnosis of a left sided lesion. Conclusion: This study identified wide variability in FS practice in local hospitals and highlighted the lack of quality standards particularly in terms of examination extent, use of medication, bowel preparation and mucosal visualisation. It showed that FS is widely practiced and a useful diagnostic tool but to make it more effective screening tool for colorectal cancer, a standardisation process is needed. Competing interests: None declared. References: 1. Atkin W, Edwards R, Kralj-Hans I, et al. Once-only flexible sigmoidoscopy screening in prevention of colorectal cancer: a multicentre randomised controlled trial. Lancet 2010;375:1624–33. 2. Hoff G, Grotmol T, Skovlund E, et al. Risk of colorectal cancer seven years after flexible sigmoidoscopy screening: randomised controlled trial. BMJ 2009;338 :b1846.